Analisis Pengaruh Beban Kerja dan Komitmen Organisasi terhadap Kinerja Karyawan melalui Turnover Intention sebagai Variabel Intervening - Ryan Aulia Authar (Universitas Muria Kudus, 2019)
Company always expects its employees to have achievements, because having employees who excel will provide optimal contributions to the company. Good human resources management will lead to achieving goals. Therefore, it is important to analyze of the influence of workload and organizational commitment on employee performance through turnover intention. The purpose of this study was to analyze the effect of workload and organizational commitment on employee performance through turnover intention, the effect of workload and organizational commitment on turnover intention directly or indirectly as an intervening variable. The sample of this study were 140 people. The sampling technique used the proportional random sampling method. Data analysis method uses Structural Equation Modeling (SEM). The results of the study are that workload has a significant positive effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. Workload has a significant positive effect on employee performance. Organizational commitment has a significant positive effect on employee performance. Turnover intention has a negative and significant effect on employee performance. Workload does not have a significant effect on employee performance through turnover intention. Organizational commitment has a significant effect on employee performance through turnover intention.